Chemical composition of essential oils from plantago lanceolata L. leaves extracted by hydrodistillation - Bajer, Tomáš; Janda, Václav; Bajerová, Petra; Kremr, Daniel; Eisner, Aleš; Ventura, Karel (Journal of food science and technology, 2016)
Extensive traditional use of medical plants leads to research dealing with chemical composition of essential oils. The aim of this work was evaluation of quality of the essential oil and extending of the knowledge about chemical composition of essential oil from ribwort (Plantago lanceolata L.) and proportional representation of compounds. Extractions of essential oils from samples of ribwort were performed by hydrodistillation. GC-MS and GC-FID techniques were used for investigation of the qualitative and semi-quantitative content of aromatic compounds in the essential oils, respectively. Major aroma constituents of ribwort leaves were groups of fatty acids 28.0-52.1 % (the most abundant palmitic acid 15.3-32.0 %), oxidated monoterpenes 4.3-13.2 % (linalool 2.7-3.5 %), aldehydes and ketones 6.9-10.0 % (pentyl vinyl ketone 2.0-3.4 %) and alcohols 3.8-9.2 % (1-octen-3-ol 2.4-8.2 %). In relative high amount were identified apocarotenoids (1.5-2.3 %) which are important constituents because of their intense fragrant. The importance is in potential manufacture control of feedstocks before producing of food supplements.
Keywords: GC-FID; Plantago lanceolata L.; Hydrodistillation; GC-MS; Essential oil